PENERAPAN TEKNOLOGI TEPAT GUNA BIO FAD’S DALAM UPAYA MENINGKATKAN PENDAPATAN NELAYAN SKALA KECIL PADA MUSIM PACEKLIK - Irman Halid; Nasruddin Djunaedi (Universitas Mataram, 2022)
The fishermen group on the coast of Karang-karangan Village, Luwu Regency, South Sulawesi is a small fishing community. Fishing activity is classified as simple and inherited from the ancestors. Fish